Making vending machines smarter with the use of Machine Learning and Artificial Intelligence: Set-up and Architectur - Istrefi, Dashmir; Zdravevski, Eftim (My University, 2020)
Vending machines conveniently provide snacks, beverages, cigarettes, food, and other items to consumers. Management of the ma chine supplies and cash is a challenging logistic process. At a time when the Internet of Things paradigm becomes omnipresent, industries are cur rently going through “The Fourth Industrial Revolution”. These things combined are also being adopted in the vending machines industry, lead ing to the development of smart vending machines. This paper presents our hoyo.ai chip thatcan be plugged into non-smart vending machines and enable them internet connectivity and other smart features. With this affordable chip, thousands of vending machines’ lifespan can be ex tended, enabling smart features such as predictive maintenance and just in-time restocking.
Keywords: Smart Vending Machines, Just-in-time restocking, Machine Learning, Predictive Maintenance